The marketing of sugar‐sweetened beverages to young people on Facebook - Aimee L. Brownbill; Caroline L. Miller; Annette J. Braunack‐Mayer (Elsevier, 2018)
Objective: We explored how sugar‐sweetened beverages are marketed to Australian young people through sugar‐sweetened beverage brand Facebook pages. Methods: We undertook a content analysis of Facebook posts made by six of the most popular sugar‐sweetened beverage Facebook pages in Australia. Data were collected for a six‐month period and were quantitatively analysed for descriptive data and explicit marketing techniques and then thematically analysed for implicit marketing messages. Results: There were almost 1.9 million engagements across the six pages over the six‐month period. Most posts (70%) included one or more calls to action through which followers were encouraged to do something. Content by sports and energy drink brands were heavily dominated by 'sporting prowess' and 'masculinity' themes while content by Coca‐Cola shared the message of 'having fun with friends' and 'happiness'. All pages used outdoor setting scenes. Conclusions: Sugar‐sweetened beverage brands use Facebook to align their marketing with the socio‐cultural values and practices likely to be regarded as important by young people. Implications for public health: Our findings provide challenges and opportunities for those in public health advocacy and policy to consider for future obesity‐reduction strategies.